INTEGRASI SOSIAL DALAM PERAYAAN TRADISI MAULID NABI DI KALANGAN MASYARAKAT DESA ROTO PROBOLINGGO - Hasan, M. Lutfiatul; Badrun, Badrun (Institut Agama Islam Sumatera Barat Pariaman, 2025)
The tradition of the Prophet's birthday is a commemoration of the birthday of the Prophet Muhammad (peace be upon him), which in Indonesia is celebrated on every 12th of Rabiul Awal in the Hijri calendar. The celebration of the Prophet's birthday is a religious ceremony and a tradition that developed among the Muslim community long after the death of the Prophet Muhammad. Actually, the commemoration of the Prophet's birthday shows gratitude and respect for the Prophet Muhammad. As for the people of Roto Village, Probolinggo Regency, who continue to carry out this tradition. This paper examines the process of implementing the Maulid Nabi and analyzes the social integration that arises with the Maulid Nabi tradition and its impact on the community. This research is a qualitative study and the author collected data in this study using historical research methods. The procedural or flow of the historical research method includes four stages, namely: heuristics, source criticism, interpretation, and historiography. The result of this research is that the Roto Village community continues to carry out hereditary traditions that are different from other regions in celebrating the Prophet's birthday. In general, the celebration of the Prophet's Maulid is only celebrated every 12th of Rabiul Awal ceremonially, but in Roto Village the celebration of the Prophet's Maulid is carried out for a whole month in the month of Maulud by rotating residents' homes in turn. this research can be concluded that social integration arises with the celebration of the Prophet's Maulid which is carried out in this way.